The use of hyaluronic acid in arthroscopy: systematic review (Research, Society and Development, 2021)
The aim of the present study was to evaluate the effectiveness of using hyaluronic acid injections after arthroscopic procedures in patients with temporomandibular disorders. The methodology used to achieve the proposed aim was a literature review currently available and conducted in MEDLINE databases via PubMed, Scopus, Scielo and Bireme, through controlled and uncontrolled terms, using Boolean operators and Descriptors in Sciences of the Health DeCS/MeSH previously chosen. After applying the search strategies and eligibility criteria, 13 articles were included and the following data were collected: author, year, study type, methodology for diagnosing temporomandibular disorder, sample size, hyaluronic acid used, use of other therapeutic agents, follow-up period and reported benefits. Interpretation of the evidence obtained in this study allowed us to conclude that the use of hyaluronic acid in arthroscopy procedures is effective and can be recommended for patients being treated for temporomandibular disorders. The need for further studies on the subject was highlighted, to establish a care standard protocol.